Haematological malignancies in relatives of patients affected with myeloproliferative neoplasms. Issue 2 (24th March 2022) - Vanni, Daniele; Borsani, Oscar; Nannya, Yasuhito; Sant'Antonio, Emanuela; Trotti, Chiara; Casetti, Ilaria Carola; Pietra, Daniela; Gallì, Anna; Zibellini, Silvia; Ferretti, Virginia Valeria; Malcovati, Luca; Ogawa, Seishi; et al.
Abstract: In a cohort of 3131 patients with myeloproliferative neoplasms (MPNs), we identified 200 patients (6.4%) who reported a second case of haematological malignancies (HM) in first‐ or second‐degree relatives. The occurrence of a second HM in the family was not influenced by MPN subtype, sex or driver mutation, while it was associated with age at MPN diagnosis: 8.5% of patients diagnosed with MPN younger than 45 years had a second relative affected with HM compared to 5.5% of those diagnosed at the age of 45 years or older ( p = 0.003), thus suggesting a genetic predisposition to HM with early onset.